2022
DOI: 10.1177/20563051221087255
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Test of the Effects of Digital Content Permanency on Perceived Anonymity and Indirect Effects on Cyber Bullying Intentions

Abstract: An online experiment was conducted to examine the causal effects of digital content permanency on perceived anonymity, as well as the correlations between perceived anonymity, perceived consequences of anonymous cyber bullying, normative beliefs about cyber bullying, and cyber bullying intentions. College students in the United States were introduced to a social media platform described as featuring either non-permanent or permanent content. Results showed participants in the non-permanent (vs. permanent) cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…For example, people are more likely to repeat cyber-incivility when nearby comments (i.e., descriptive norms) and “up votes” (i.e., injunctive norms; Rains et al, 2017) affirm their behavior. Perpetrators who believe their friends approve of cyberbullying (i.e., it is normative) are likelier to engage in the behavior (Yu & Riddle, 2022). Comparatively, cyberloafing decreases when employees believe coworkers and supervisors do not support it (Liberman et al, 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, people are more likely to repeat cyber-incivility when nearby comments (i.e., descriptive norms) and “up votes” (i.e., injunctive norms; Rains et al, 2017) affirm their behavior. Perpetrators who believe their friends approve of cyberbullying (i.e., it is normative) are likelier to engage in the behavior (Yu & Riddle, 2022). Comparatively, cyberloafing decreases when employees believe coworkers and supervisors do not support it (Liberman et al, 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Empirical research has also found that the anonymity inherent in social media use is linked to deindividuation and increased cyberbullying (Lowry et al, 2016). Perpetrators are more likely to engage in cyber-aggression using online accounts (Lapidot-Lefler & Barak, 2012), video clips (Slonje & Smith, 2008), social media (Yu & Riddle, 2022), online blogs (Zimmerman & Ybarra, 2016), and Twitter (Fox et al, 2015) when they are anonymous. In addition, Gardner et al (2016) found that (un)accountability reflected in employees’ perceptions of an organization’s ineffective responses to reports of cyber-aggression was positively related to engagement in workplace cyberbullying.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the study chose perceived anonymity as the predictor of different bystander subcategories, starting from individual factors. Perceived anonymity refers to one’s belief in their ability to maintain an unrecognizable status in a specific digital environment [ 17 ]. Due to the online disinhibition effect, perceived anonymity can reduce the cost and adverse consequences of online behavior, leading individuals to engage in more unconstrained online behavior.…”
Section: Introductionmentioning
confidence: 99%